THE EFFECTIVENESS OF THIEVES STRATEGY TOWARDS STUDENTS’ READING COMPREHENSION AT THE ELEVENTH GRADE OF SMAN 19 TEBO - Rauldatul Husni; Lina Candra Wati (Universitas Putera Batam, 2021)
This research explore the Effectiveness of “thieves” Strategy Towards Students’ Reading Comprehension at the Eleventh Grade of SMAN 19 Tebo. The problems of this research are students lack of vocabulary, students did not have good motivation in reading text and the students have difficulty in comprehending texts. The purpose of the research is to know the effectiveness of THIEVES strategy towards students’ reading comprehension at the eleventh grade of SMAN 19 Tebo. This research focus on the quantitative research. The population in this study all 11 grades at SMAN 19 Tebo. In this study, the total population is 29, consist of class 11 IPS and 11 MIPA. Then, the sample in this study 11 IPS and II MIPA. Based on practical teaching English at SMAN 19 Tebo, the researcher find some problems in the class. Therefore the researcher applies strategy in reading, with this strategy students learn the THIEVES strategy before students read the text. The research findings indicate that the use of THIEVES strategy was able to improve the students’ reading comprehension. The conclusions of this research is supported by the post-test results of students’ reading comprehension at the eleventh grade students of SMAN 19 Tebo. The mean post-test experimental class is 78.75 and in the control class is 71.69. The differerence score between experimental class and control class was 7.06. The researcher find a positive impact on the experimental class. It means that students’ reading comprehension in experimental class was significantly improve and there is significantly different effect between experimental class and control class which teach by using THIEVES and without THIEVES. It indicates that the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted. It presents that the THIEVES strategy give a significant effect on students’ reading comprehension of report text.